Knowledge, attitude and practices regarding pulmonary tuberculosis in a rural area of Tamil Nadu, India: a cross sectional study - G., Angeline Grace; S., Gopalakrishnan; R., Umadevi (International Journal Of Community Medicine And Public Health, 2018)
Background: Tuberculosis is still a major public health problem in India. Lack of knowledge about the cause, risk factors, treatment and prevention of pulmonary TB is a major challenge to be addressed to reduce disease transmission. This study was planned with the objective of determining the Knowledge, Attitude and Practices regarding pulmonary tuberculosis in a rural population of Kancheepuram district, Tamilnadu, India. Methods: This community based cross sectional study was carried out between January and March 2018. Sample size of 400 was calculated by using formula 4pq/d2 and respondents were selected from sampled households using systematic random sampling. Data were collected using a pre-tested, structured questionnaire, which were analyzed using SPSS version 16.0 and presented using descriptive and analytical statistics. Results: Among 400 participants studied, only 45.5% had adequate knowledge on PTB, 14.7% had positive attitude and 26.5% had good practices towards PTB. About 91.5% had heard about TB and 79% knew that TB could be transmitted from a patient to others. The cause for TB was correctly mentioned by only 19.5% of the subjects. About 35% knew that transmission of TB is preventable. Positive attitude had a statistically significant association with higher socioeconomic class and with adequate knowledge. Good practices on TB were more noted among participants with adequate knowledge and with age ≤45 years. Conclusions: Study respondents had basic awareness about pulmonary TB but knowledge on cause and prevention was inadequate. Their attitude and practices towards TB also need to be improved. Health education activities need to be intensified for the rural population to bring about significant change in their level of awareness on TB.